X-linked ichthyosis presenting as erythroderma: A rare case - Anirban Das; Vivek Mishra; Kaushik Shome; Arpita Sen (Wolters Kluwer Medknow Publications, 2015)
X-linked ichthyosis is a rare form of dermatological disease and when it presents as erythroderma it is even rarer. History of consanguineous marriage and prolonged labor during birth of patient, generalized scaling which gets better in summer months, flexural involvement, cryptorchidism made a diagnosis of X-linked ichthyosis. We report this case because of its rarity as erythroderma.